Influence of process conditions on the physicochemical properties of honey powder produced by spray drying - Madai Bringas-Lantigua; Jorge A. Pino; Yojhansel Aragüez-Fortes (Revista CENIC Ciencias Químicas, 2016)
The influence of inlet and outlet air temperatures on the physicochemical properties of spray dried honey was evaluated by using a three-level factor design. The independent variables were: inlet air temperature (130-170oC) and outlet air temperature (75-85oC). The process was carried out on a rotary atomizer spray dryer and with maltodextrin 9DE as carrier agent. Factors such as moisture content, cohesiveness, hygroscopicity, solubility and hydroxymethylfurfural content were used as quality attributes of the honey powders. Powder moisture and solubility time were negatively affected by inlet and outlet air temperatures, which are directly related to heat and mass transfer. Powders cohesiveness, hygroscopicity and hydroxymethylfurfural increased with increasing both temperatures. The multiple response optimisation indicated that an inlet air temperature of 144 oC and an outlet air temperature of 85 oC were predicted to provide the minimal moisture content (1.4 % wb dry basis), cohesiveness (1.34), solubility time (62 s), hygroscopicity (25.4 g/100 g), and hydroxymethylfurfural (15.3 mg/kg). The particles have a higher degree of uniformity regarding shape and good distribution (average particle size D43 = 16.1 ± 0.4 μm).